GUGUS KENDALI MUTU - Hadis Purba; Ikri Malia (Universitas Dharmawangsa, 2020)
The Quality Control Cluster is also a method used to solve a problem in the process of improving quality or quality on a regular, voluntary and continuous basis in the field of work by applying the principles and techniques of quality control. Quality itself is one of the characteristics of a product or service that is determined by consumers. Efforts to improve the quality and productivity as well as the performance of a work unit going up the business world and the bureaucracy, need to be carried out continuously so that it can function and achieve its objectives optimally. The stages of the problem solving process in the Quality Control Cluster (GKM) include: 1) Collecting work-related problems, 2) Selecting and setting priority problems to be solved, 3) Setting Targets for Problems to be resolved, 4) Arranging problem solving activity plans, 5) Recommending Solutions or Problem Solving Plans to Company Management, 6) Implementing and implementing problem solving measures that have been approved by the Company's Management, 7) Monitoring and Evaluation of the results of the Implementation, 8) Standardizing.